A review of contemporary practice and proficiency with Gram staining in anatomical pathology laboratories. (3rd April 2017) - Peck, Martyn; Badrick, Tony
Abstract: The classical Gram stain was originally established in 1884 by Hans Christian Gram following which numerous modifications have been developed, typically with specific sample types in mind. Gram methods such as Brown–Hopps, Brown–Brenn, and Gram–Twort have been commonly adopted for routine use in anatomical pathology laboratories, enabling the simultaneous demonstration and identification of Gram-positive and Gram-negative organisms in histological sections. The various Gram methods available to laboratories each necessitate practical and interpretative skill by laboratory staff. In addition to staff competencies, the methods require the use of appropriate control material, i.e. ideally comprising Gram-positive and Gram-negative bacteria. An integral component of laboratory annual accreditation involves the auditing of technical and procedural competency, including participation in an external quality assurance activity. In 2011 and 2016 RCPAQAP Anatomical Pathology (The Royal College of Pathologists of Australasia Quality Assurance Programs) provided its participants a Gram stain exercise, which was repeated later in the same years. This has afforded participant laboratories a valuable opportunity to review and improve on their initial performance, as resulted by the RCPAQAP Technical Module advisory committee, in conjunction with their routine protocol for that special stain. The data derived from these years have enabled a comprehensive insight of contemporary practice of Gram staining in many anatomical pathology laboratories, while also enabling an appraisal of individual and generalized laboratory performance with Gram staining. A review of contemporary Gram stain methods in use in anatomical pathology laboratories was undertaken, and performance in their execution.